2021
DOI: 10.1002/jmr.2921
|View full text |Cite
|
Sign up to set email alerts
|

SERS and DFT studies of 2‐(trichloroacetyl)pyrrole chemisorbed on the surface of silver and gold coated thin films: In perspective of biosensor applications

Abstract: The adsorption and orientations of 2-(trichloroacetyl)pyrrole (TCAP) adsorbed on a fabricated silver-coated thin film (SCF), and gold-coated thin film (GCF) were investigated using surface-enhanced Raman scattering (SERS) studies and compared with the normal Raman scattering (nRs) spectrum of TCAP. The observed nRs and SERS spectra of TCAP were validated theoretically using DFT quantum chemical calculations. Initially, the molecular structure of TCAP, TCAP-Ag 3 , and TCAP-Au 4 molecular systems were optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The DFT approach is increasingly used for SERS spectroscopy by several research groups, as demonstrated by the most recent studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in which close links between DFT calculations and SERS applications are shown. Among these studies, the following studies devoted to applications in sensors, especially for environmental protection, and to applications in biomedicine, are worthy of particular attention.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…The DFT approach is increasingly used for SERS spectroscopy by several research groups, as demonstrated by the most recent studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] in which close links between DFT calculations and SERS applications are shown. Among these studies, the following studies devoted to applications in sensors, especially for environmental protection, and to applications in biomedicine, are worthy of particular attention.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…[20] Furthermore, the investigation of the adsorption and orientations of 2-(trichloroacetyl)pyrrole (TCAP) on silver-coated and gold-coated thin films using surfaceenhanced Raman scattering (SERS) provides valuable insights for the development of active SERS substrates and pyrrolerelated biosensors, with potential applications in chemical analysis and biosensing. [21] In-silico methods have been successfully incorporated with drug discovery research since they can analyze complex biological and chemical systems. [22] A combination of computational and experimental methods is also frequently used to identify and develop new promising compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the pyrrole‐2,3‐dicarboxylate‐based compounds are explored in terms of the capability of using them as potential anti‐cancer agents against hepatic carcinoma, employing computational drug design techniques and experimental analyses; the synthesized compounds demonstrated significant anti‐hepatic carcinoma activity, indicating their potential as novel therapeutic candidates for treating liver cancer [20] . Furthermore, the investigation of the adsorption and orientations of 2‐(trichloroacetyl)pyrrole (TCAP) on silver‐coated and gold‐coated thin films using surface‐enhanced Raman scattering (SERS) provides valuable insights for the development of active SERS substrates and pyrrole‐related biosensors, with potential applications in chemical analysis and biosensing [21] …”
Section: Introductionmentioning
confidence: 99%